2021
DOI: 10.1016/j.gore.2021.100870
|View full text |Cite
|
Sign up to set email alerts
|

Survival impact of bowel resection at the time of interval cytoreductive surgery for advanced ovarian cancer

Abstract: Highlights Bowel resection is associated with decreased three-year survival. Bowel resection does not impact progression free survival. Bowel resection is associated with significant peri -operative complication. Sequelae of peri -operative morbidity may contribute to decreased survival. Bowel resection may be a surrogate for worse tumor molecular su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 32 publications
(47 reference statements)
2
2
0
Order By: Relevance
“…Age and surgical outcome were found to be independently associated with survival, which is in correspondence with available evidence 7,22,23 . These factors did not differ between groups, explaining that a similar OS was seen in the trial population and the real‐world population.…”
Section: Discussionsupporting
confidence: 83%
“…Age and surgical outcome were found to be independently associated with survival, which is in correspondence with available evidence 7,22,23 . These factors did not differ between groups, explaining that a similar OS was seen in the trial population and the real‐world population.…”
Section: Discussionsupporting
confidence: 83%
“…The risk of complications after intestinal resection is higher than in patients without intestinal resection, and the incidence of complications after multiple intestinal resection was found to be higher than that of single intestinal resection, mainly comprising the following complications: infection, sepsis, pelvic abscess, respiratory distress, pulmonary embolism, anastomotic rupture, intestinal fistula [12,[20][21][22]. Our study showed consistent results where complications happened in nearly half of the patients in both groups, which were at a higher level.…”
Section: Discussionsupporting
confidence: 80%
“…There we found was no significant difference in the ICU admission rate and length of ICU stay between the ERAS group and the control group. However, compared with the control group, the patients from the ERAS group had a shorter median time interval from surgery to postoperative chemotherapy, 16 (9)(10)(11)(12)(13)(14)(15)(16)(17)(18) days vs. 20 (10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24) days (p = 0.042), and so as the hospital stay, 20 (18-21) days vs. 24 (19)(20)(21)(22)(23)(24)(25)(26)(27)(28) days (p = 0.025). The rate of Clavien-Dindo level I-II complications was 38.9% and 40.9%, respectively, (p = 0.897), and the main types of Clavien-Dindo level I-II complications were anemia, hypoalbuminemia, fever and pain, which were corrected after active medical management.…”
Section: Postoperative Outcomesmentioning
confidence: 96%
“…Reports of intestinal resection have been published to increase optimal debulking surgery rates and improve patient survival [40] [41], however, extension of the surgical scope is associated with higher rates of intraoperative and early postoperative complications (e.g., bleeding, anastomotic dehiscence, and infection) [42]. The long-term sequelae of perioperative morbidity of intestinal resection may lead to increased mortality, and intestinal resection may be a negative prognostic factor [43]. Fistulas are sometimes performed after intestinal resection, which significantly reduces the comfort of the patient.…”
Section: Intestinal Surgerymentioning
confidence: 99%